Ultrasonic vibration-assisted pelleting of cellulosic biomass for ethanol manufacturing - Zhang, Pengfei (Kansas State University, 2011)
Both the U.S. and world economies have been depending on petroleum based liquid transportation fuels (such as gasoline, diesel, and jet fuels), which are finite and nonrenewable energy sources. Increasing demands and concerns for the reliable supply of liquid transportation fuels make it important to find alternative sources to petroleum based fuels. One such alternative is cellulosic ethanol. Research, development, and production of cellulosic ethanol have received significant support from both the U.S. government and private investors. However, several technical barriers have hindered large-scale, cost-effective manufacturing of cellulosic ethanol. One such barrier is related to the low density of cellulosic feedstocks, causing high cost in their transportation and storage. Another barrier is the lack of efficient pretreatment procedures, making pretreatment one of the most expensive processing steps and causing efficiency in the subsequent enzymatic hydrolysis to be very low. There is a crucial need to develop more cost-effective processes to manufacture cellulosic ethanol. Ultrasonic vibration-assisted (UV-A) pelleting can increase not only the density of cellulosic feedstocks but also sugar and ethanol yields. It can help realize cost-effective manufacturing of cellulosic ethanol. This PhD research consists of eleven chapters. Firstly, an introduction of this research is given in Chapter 1. Secondly, a literature review on ultrasonic pretreatment for ethanol manufacturing is given in Chapter 2 to show what has been done in this field. Thirdly, a feasibility test on UV-A pelleting of cellulosic biomass is conducted in Chapter 3. Comparisons of the pellet density and sugar yield are also made between pelleting with and without ultrasonic vibration. Next, effects of process variables (such as biomass moisture content, biomass particle size, pelleting pressure, and ultrasonic power) on output variables (such as pellet density, durability, stability, and sugar yield) have been studies in Chapters 4~6. Chapter 7 compares sugar yields between two kinds of materials: pellets processed by UV-A pelleting and biomass not processed by UV-A pelleting under different combinations of three pretreatment variables (temperature, processing time, and solid content). Next, mechanisms through which UV-A pelleting increases sugar and ethanol yields are investigated in Chapters 8 and 9. Then, a predictive model of pellet density is developed for UV-A pelleting in Chapter 10. Finally, conclusions are given in Chapter 11.
Keywords: Biofuel; Ethanol; Pelleting; Ultrasonic vibration; Mechanical Engineering (0548)